2015
DOI: 10.1063/1.4929344
|View full text |Cite
|
Sign up to set email alerts
|

Topographically generated internal waves and boundary layer instabilities

Abstract: Flow over topography has been shown to generate finite amplitude internal waves upstream, over the topography and downstream. Such waves can interact with the viscous bottom boundary layer to produce vigorous instabilities. However, the strength and size of such instabilities depends on whether viscosity significantly modifies the wave generation process, which is usually treated using inviscid theory in the literature. In this work, we contrast cases in which boundary layer separation profoundly alters the wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…It is generally thought that GI requires a threshold strength of APG (Diamessis & Redekopp, 2006), and this is influenced by wave shape and amplitude (Stastna & Lamb, 2008). The waves in previous GI studies have largely focused on large‐amplitude steady soliton solutions to either WNL (e.g., Diamessis & Redekopp, 2006) or fully nonlinear equations (Stastna & Lamb, 2002, 2008) (a recent notable exception is Soontiens et al, 2015, who demonstrated instability under relatively low‐amplitude developing waves near to their generation source). While our NLIWs were large amplitude, they were complex, time‐evolving wave trains and not well described by such steady equations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is generally thought that GI requires a threshold strength of APG (Diamessis & Redekopp, 2006), and this is influenced by wave shape and amplitude (Stastna & Lamb, 2008). The waves in previous GI studies have largely focused on large‐amplitude steady soliton solutions to either WNL (e.g., Diamessis & Redekopp, 2006) or fully nonlinear equations (Stastna & Lamb, 2002, 2008) (a recent notable exception is Soontiens et al, 2015, who demonstrated instability under relatively low‐amplitude developing waves near to their generation source). While our NLIWs were large amplitude, they were complex, time‐evolving wave trains and not well described by such steady equations.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond mobilization of bed load, Bogucki et al (1997) observed the potential for NLIWs to eject sediments high in the water column, and Bogucki and Redekopp (1999) subsequently proposed that this was due to a global instability (GI) mechanism. This GI mechanism has motivated nearly two decades of laboratory (Aghsaee & Boegman, 2015; Carr et al, 2008) and numerical (Aghsaee et al, 2012; Diamessis & Redekopp, 2006; Stastna & Lamb, 2002) studies and, more recently, studies into other novel NLIW‐induced instabilities (Harnanan et al, 2015, 2017; Olsthoorn & Stastna, 2014; Soontiens et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that some wave drag in the boundary layer can be significant was also recognized by [16] and earlier by [17]. Beyond the drag itself, the contribution of boundary layer waves to turbulent exchange is also recognized in oceanography and for sediment suspension [18,19].…”
Section: Introductionmentioning
confidence: 82%
“…Local instability made by internal solitary waves interacting with a variable bottom topography may exhibit jet-like roll-up of vorticity near the crest of the topography, as calculated in two and three dimensions at moderate Reynolds number by Harnanan, Soontiens & Stastna (2015) and Harnanan, Stastna & Soontiens (2017). Re-suspension or entrainment of internal solitary waves interacting with a bottom topography was modelled numerically by Olsthoorn &Stastna (2014), andWaite (2015) calculated the viscous bottom boundary layer effects on the generation of internal solitary waves at topography and the related instabilities in the case of a background current.…”
Section: Review Of Internal-wave-driven Instability In the Bottom Bou...mentioning
confidence: 99%